EXPOSURE TO LEPTOSPIRA SP. IN VETERINARY STUDENTS AT THE BEGINNING AND AT THE END OF THE CAREER - Dammert B., Nicole (2009)
Leptospirosis is globally known as the most prevalent zoonotic disease, caused by different Leptospira sp. serovars. In urban areas, exposure is mainly related to certain occupational health groups, such as veterinary students. The objective of the research was to determine the rate of serorreactors to leptospira in veterinary students on two stages of their studies, at the beginning (sophomore students) and at the end (senior students). Pool serum samples were analized by the microagglutination test (MAT) for serovars canicola, icterohemorragiae, grippotyphosa, georgia, pomona and hardjo. Positive result were 18.4% (7/38) for sophomore students and 8.8% (7/80) for seniors. The positive serovars were georgia for the sophomore students, and georgia, icterohemorragiae and canicola for the seniors. The risk of infection was 2.4 (0.76 – 7.28) (p=0.137) comparing sophomore versus seniors. Exposure to Leptospira infection was demonstrated in veterinary students showing the need for more research on the main risk factors related to its presentation.